Forming New Vowel Categories in Second Language Speech: The Case of Polish Learners’ Production of English /I/ and /e/ - Rojczyk, Arkadiusz (Research in Language, 2010)
The paper concentrates on formation of L2 English vowel categories in the speech of Polish learners. More specifically, it compares distribution of two English categories - /I/ and /e/ relative to neighbouring Polish vowels. 43 participants recorded Polish and English vowels in a /bVt/ context. First two formants were measured at a vowel midpoint and plotted on a vowel plane. The results reveal that while a separate /I/ category is formed fairly effectively in Polish learners pronunciation of English, a category of /e/ is almost completely subsumed by a Polish vowel /ϵ/